Cascaded Mach–Zehnder interferometer tunable filters. (11th May 2016) - Ovvyan, A P; Gruhler, N; Ferrari, S; Pernice, W H P
Abstract: By cascading compact and low-loss Mach–Zehnder interferometers (MZIs) embedded within nanophotonic circuits we realize thermo-optically tunable optical filters for the visible wavelength range. Through phase tuning in either arm of the MZI, the filter response with maximum extinction can be shifted beyond one free-spectral range with low electrical power consumption. The working wavelength of our device is aligned with the emission wavelength of the silicon vacancy color center in diamond around 740 nm where we realize a filter depth beyond 36.5 dB. Our approach allows for efficient isolation of the emitted signal intensity in future hybrid nanodiamond-nanophotonic circuits.